The Application of Formative Assessment in High School English Reading Teaching - Changxia, Ke (International Journal of Humanities and Education Development (IJHED), 2023)
Teaching evaluation is a very important part of high school English teaching. Curriculum assessment has an important impact on students' learning effectiveness and achievement. The current research on English reading teaching dominated by summative assessment only focuses on the strategic research on how to promote the improvement of English reading ability in schools, which makes it difficult for students to form good reading habits. Compared with summative assessment, formative assessment can enable high school students to participate more fully in the classroom, and to a certain extent, effectively improve high school students' interest and mastery of English reading, so as to improve high school students' English reading ability. Using formative assessment in the English reading classroom can better help students learn English reading and achieve better classroom results